2019
DOI: 10.1111/aogs.13712
|View full text |Cite
|
Sign up to set email alerts
|

Balloon catheter vs oxytocin alone for induction of labor in women with a previous cesarean section: A randomized controlled trial

Abstract: Abbreviations: BC, balloon catheter; PROM, premature rupture of membranes; VBR, vaginal birth rate. CorrespondenceAbstract Introduction: The aim of this study was to compare the efficacy and maternal-neonatal morbidity between balloon catheter and oxytocin for induction of labor in women with a previous cesarean section and an unfavorable cervix. Material and methods:This open-label randomized controlled trial took place in seven French hospitals. Inclusion criteria were medical indication for labor induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
0
12
0
10
Order By: Relevance
“…A randomised controlled multicentre study compared induction of labour with the Foley catheter (n = 101, left in place for 12 h) in women with previous Caesarean section and unripe cervix (BS ≤ 4) to labour induction with intravenous oxytocin at increasing doses (n = 103) ( [35], LoE Ib). Endpoint of the study was the rate of vaginal deliveries, which was significantly higher following the use of balloon catheters (50.0 %) compared to the administration of intravenous oxytocin (37 %); there were no signficant differences in uterine rupture rates or perinatal outcomes between groups (▶ Table 1).…”
Section: Comparison Of Induction Of Labour With Balloon Catheter Vs I...mentioning
confidence: 99%
“…A randomised controlled multicentre study compared induction of labour with the Foley catheter (n = 101, left in place for 12 h) in women with previous Caesarean section and unripe cervix (BS ≤ 4) to labour induction with intravenous oxytocin at increasing doses (n = 103) ( [35], LoE Ib). Endpoint of the study was the rate of vaginal deliveries, which was significantly higher following the use of balloon catheters (50.0 %) compared to the administration of intravenous oxytocin (37 %); there were no signficant differences in uterine rupture rates or perinatal outcomes between groups (▶ Table 1).…”
Section: Comparison Of Induction Of Labour With Balloon Catheter Vs I...mentioning
confidence: 99%
“…This will allow for standardized protocols to be followed, thus mitigating differences in outcomes due to variations in clinical practice, increasing the generalizability of our findings. For example, cervical ripening is regularly used in women with one previous cesarean delivery in France [26][27][28]. In our team, women with one previous cesarean delivery are not contraindicated to mechanical device and its practice is usual and well framed [29].…”
Section: Discussionmentioning
confidence: 98%
“…94 In a small trial comparing cervical ripening methods for people with a previous cesarean birth and low Bishop score, French investigators found that the balloon catheter was associated with a higher probability of vaginal birth than low-dose intravenous oxytocin. 95 . How should induction of labor techniques be adapted when caring for pregnant persons who are obese?…”
Section:  How Long Should I Continue To Use Cervical Ripening Methods During Induction Of Labor Before Starting Synthetic Oxytocin To Inmentioning
confidence: 99%
“…Synthetic oxytocin and osmotic dilator devices may also be used for cervical ripening and to stimulate uterine contractions in these persons 94 . In a small trial comparing cervical ripening methods for people with a previous cesarean birth and low Bishop score, French investigators found that the balloon catheter was associated with a higher probability of vaginal birth than low‐dose intravenous oxytocin 95 …”
Section: Introductionmentioning
confidence: 99%